1998
DOI: 10.1046/j.1365-246x.1998.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermomagnetic behaviour of haematite and goethite as a function of grain size in various non-saturating magnetic fields

Abstract: When interpreting thermomagnetic curves of non‐saturated magnetic minerals, irreversible heating and cooling curves need not necessarily imply chemical or structural changes. Increased aligning of magnetic moments on heating in an applied magnetic field can also induce an irreversible cooling curve. The two processes can be distinguished by stirring the sample between subsequent thermomagnetic runs. Sample redispersion considerably enhances the interpretative value of thermomagnetic analysis and is therefore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 31 publications
8
40
0
1
Order By: Relevance
“…3); thermal studies confirmed this result. This ferrimagnetic phase was also detected in synthetic hematites in other studies (de Boer and Dekkers, 1998;France and Oldfield, 2000). The material was thermally treated in order to remove (minimise) the ferrimagnetic phase (possibly magnetite or maghemite) without affecting the hematite; it was heated in air up to 750 • C. After this process, a new sample, HmSth3, was prepared by using the treated material.…”
Section: Synthetic and Natural Samplessupporting
confidence: 79%
“…3); thermal studies confirmed this result. This ferrimagnetic phase was also detected in synthetic hematites in other studies (de Boer and Dekkers, 1998;France and Oldfield, 2000). The material was thermally treated in order to remove (minimise) the ferrimagnetic phase (possibly magnetite or maghemite) without affecting the hematite; it was heated in air up to 750 • C. After this process, a new sample, HmSth3, was prepared by using the treated material.…”
Section: Synthetic and Natural Samplessupporting
confidence: 79%
“…VSM analysis indicates that the saturation magnetisation per kilogram of the magnetic iron oxide core is of 76.16 emu/g. The value is close to the literature value of bulk Fe 3 O 4 , which is about 92 emu/g [22]. Also, the measured remanence of these nanoparticles is 4.5 A m 2 /kg and coercivity is 15.3 k A/m.…”
Section: Nanoparticles Characterisationsupporting
confidence: 88%
“…These are argued to form as synsedimentary authigenic precipitates in oxic environments [Walker et al, 1981]. Both the specular hematite nodules and the subhedral to euhedral platy hematite crystals of the microrosette have micron to submicron sizes (compare crystals shown by Maher and Thompson [1999]) and correspond to SD hematite [e.g., de Boer and Dekkers, 1998]. …”
Section: Microcrystalline Hematitementioning
confidence: 99%